2016
DOI: 10.7150/thno.14792
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Anti-Tumor Efficacy through a Combination of Integrin αvβ6-Targeted Photodynamic Therapy and Immune Checkpoint Inhibition

Abstract: “Training” the host immune system to recognize and systemically eliminate residual tumor lesions and micrometastases is a promising strategy for cancer therapy. In this study, we investigated whether integrin αvβ6-targeted photodynamic therapy (PDT) of tumors using a phthalocyanine dye-labeled probe (termed DSAB-HK) could trigger the host immune response, and whether PDT in combination with anti-PD-1 immune checkpoint inhibition could be used for the effective therapy of primary tumors and metastases. By near-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
101
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(108 citation statements)
references
References 40 publications
6
101
0
1
Order By: Relevance
“…A study combining local radiotherapy with immunomodulatory antibodies indicated that the enhanced therapeutic efficacy was mediated by tumor antigen cross-presentation by dendritic cells to CD8 þ T cells (19). Enhanced systemic efficacy of PDT combined with immune checkpoint blockade has been reported using experimental setups involving surgical resection of PDTtreated tumors or advanced nanocarrier systems (20)(21)(22). Here, we combined local PDT with systemic CTLA-4 blockade in two independent tumor models to improve the therapeutic outcome in double-tumor-bearing mice.…”
Section: Discussionmentioning
confidence: 99%
“…A study combining local radiotherapy with immunomodulatory antibodies indicated that the enhanced therapeutic efficacy was mediated by tumor antigen cross-presentation by dendritic cells to CD8 þ T cells (19). Enhanced systemic efficacy of PDT combined with immune checkpoint blockade has been reported using experimental setups involving surgical resection of PDTtreated tumors or advanced nanocarrier systems (20)(21)(22). Here, we combined local PDT with systemic CTLA-4 blockade in two independent tumor models to improve the therapeutic outcome in double-tumor-bearing mice.…”
Section: Discussionmentioning
confidence: 99%
“…Quenching agents like this are attractive features for PDT because they attenuate singlet oxygen generation outside of the tumor site, thereby improving specificity and limiting off‐target cytotoxicity . In another study, Gao et al investigated the effects of αvβ 6 integrin‐targeted PDT on host immune response. The authors demonstrated that integrin‐targeted PDT using IRDye700‐streptavidin–biotin–HK peptide (DSAB‐HK) could both inhibit tumor growth and stimulate the host antitumor response by promoting dendrite maturation and T‐lymphocyte recruitment.…”
Section: Targeting the Tumor Microenvironment With Photochemistrymentioning
confidence: 99%
“…In addition to passive targeting tumor cells, formulations can be exploited to actively target specific tumor site by coating specific surface receptors or conjugating motifs with target function which could reduce the off‐target effect caused by combining ICB. Two groups have reported that tumor integrin alphavbeta6‐targeting peptide (the HK peptide)–modified functional nanomaterials to augment the therapeutic effects of PDT and ICB could actively trigger the treatment of primary and metastatic tumors by activating dendritic cells to produce cytokines . Gao et al developed an IRDye700‐coupled NIRF probe with the decoration of HK peptide .…”
Section: Biomaterial‐based Strategy Integrated With Icb For Synergistmentioning
confidence: 99%
“…Two groups have reported that tumor integrin alphavbeta6‐targeting peptide (the HK peptide)–modified functional nanomaterials to augment the therapeutic effects of PDT and ICB could actively trigger the treatment of primary and metastatic tumors by activating dendritic cells to produce cytokines . Gao et al developed an IRDye700‐coupled NIRF probe with the decoration of HK peptide . Interestingly, through specific targeting of integrin avβ6, this cancer phototherapy approach could be used for diagnostic imaging and cancer therapy.…”
Section: Biomaterial‐based Strategy Integrated With Icb For Synergistmentioning
confidence: 99%